2021
DOI: 10.1016/j.matpr.2020.11.189
|View full text |Cite
|
Sign up to set email alerts
|

A brief discussion on the tensile creep deformation behaviour of wrought single-phase γ-TiAl

Abstract: Creep deformation behaviour in single phase c-TiAl alloy has been an extensively studied topic since the late 1970 s. A lot of literatures have reported creep behaviour of c-TiAl alloys, manufactured using different processing techniques [1][2][3][4][5][6][7]. The present discussion revisits the original work on understanding the tensile creep deformation behaviour of wrought single-phase c-TiAl alloy by Hayes et al. [8] and is aimed to develop an understanding of steady state creep, through strain vs strain r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Moreover, a Ref. [28]), it may be inferred that a decrease in the creep activation energy (for both Coble and NH creep) significantly reduces the creep life of the material with increasing stress levels from 69.4-103.4 MPa.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, a Ref. [28]), it may be inferred that a decrease in the creep activation energy (for both Coble and NH creep) significantly reduces the creep life of the material with increasing stress levels from 69.4-103.4 MPa.…”
Section: Resultsmentioning
confidence: 93%
“…2) with the aforementioned reports (Refs. [1], [28]), it may be inferred that M-G based approach to determine the creep life also predicts that tr decreases with increasing stress levels (from 69.4 to 103.4 MPa) at 832 Based on the Ashby's model [13], [14], [38], [39], the constitutive equation for NH (or lattice diffusion creep) is given as:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14], [16], [33]- [37]). Hayes and Martin [1] and Saha [28] have reported that ε̇ decreases with increasing stress levels (from 69.4-103.4 MPa) at 832 °C . Moreover, Saha [28] has reported that the creep mechanisms operating at different stress levels (69.4 and 103.4 MPa) at 832 °C are independent of each other and hence, are not sequential.…”
Section: Resultsmentioning
confidence: 97%
“…where, ε̇is the steady state creep rate (~ ε̇ based on the justification that many metallic materials may not exhibit steady-state creep (provided in Ref. [28])), tr is the rupture time (expressed in seconds) and (~1.40 at 832 °C ) is the M-G constant (obtained from Ref.…”
Section: Theoretical Analysismentioning
confidence: 99%